Pengenalan Rumah Adat Nusantara Berbasis Mobile AR - Fardani Annisa Damastuti; Jauari Akhmad Nur Hasim; Irma Wulandari; Darmawan Aditama; Aji Sapta Pramulen; Ibrohim Yofid Fananda; Dita Aulia Rahma (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
A traditional house is a house that has a characteristic building that symbolizes the culture of a region. The uniqueness of traditional houses in Indonesia is one of the learning materials for students in Indonesia. Books that are a medium for introducing traditional houses in Indonesia still have shortcomings in the form of limited visual display of traditional houses. So that it reduces children's interest in recognizing the traditional houses of the archipelago. This can lead to cultural erosion. Therefore, to increase interest and insight into the culture of this traditional house, technology and culture are combined. This combination uses augmented reality technology to introduce the traditional houses of the archipelago. Traditional houses are visualized through 3-dimensional objects in the android application. The augmented reality application developed is dynamic, so that the addition of content can be done without modifying the program code. This application will visualize 9 traditional houses from 9 provinces in Java, Nusa Tenggara, and Bali. The test results show an increase in knowledge of SDN Banjarmendalan students by 56% which means the application is quite effective to help students recognize the traditional houses of the archipelago and from the assessment of student satisfaction with the application get a score of 90.5% which means the application is enough to attract students to learn to recognize traditional houses.